Predictive Direct Power Control of Three-Phase Pulsewidth Modulation (PWM) Rectifier Using Space-Vector Modulation (SVM) - Bouafia, Abdelouahab; Gaubert, Jean-Paul; Krim, Fateh (IEEE transactions on power electronics, 2010)
In this paper, we present a direct power control (DPC) of three-phase pulsewidth modulation rectifier with constant switching frequency using space-vector modulation (SVM). The developed DPC scheme is based on the predictive control strategy to achieve direct control of instantaneous active and reactive power of the converter. For this purpose, at the beginning of each switching period, the required rectifier average voltage vector allowing the cancellation of active and reactive power tracking errors, at the end of the switching period, is calculated by means of predictive control algorithm in the sense of deadbeat control. The main advantages of the proposed control, compared to the works published in this subject, are that no need to use predefined switching table and voltage vector or virtual flux position, PI-based active and reactive power control loops are not necessary and constant-switching frequency. The proposed predictive direct power control was tested both in simulations and experimentally and compared with DPC using switching table. Results have proved excellent performance, and verify the validity of the proposed DPC scheme, which is much better than conventional DPC using switching table.